PENGARUH PENGHINDARAN PAJAK DAN PERATAAN LABA, TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL PEMODERASI (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2016 – 2018) - Hangtuah, Frenky Yosua; Yazid, Helmi; Taqi, Muhamad (Pascasarjana Universitas Sultan Ageng Tirtayas, 2020)
This study aims to determine the effect of tax avoidance and income smoothing on the firm value with a debt policy variable as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange which published financial statements for the period 2016-2018. By using purposive sampling technique, 243 company samples were obtained and analyzed using multiple linear regression. The results of this study indicate that (1) tax avoidance does not have a positive effect on firm value (2) Income smoothing has a positive effect on firm value (3) Debt policy as a moderating variable can strengthen the relationship between tax avoidance and firm value. (4) Debt policy as a moderating variable does not significantly strengthen the relationship between income smoothing and firm value.